ОБ ОДНОМ ПОДХОДЕ ПРИМЕНЕНИЯ ЧИСЛЕННО-АНАЛИТИЧЕСКОГО МЕТОДА К КРАЕВЫМ ЗАДАЧАМ ДЛЯ ИНТЕГРО-ДИФФЕРЕНЦИАЛЬНЫХ УРАВНЕНИЙ ТИПА ВОЛЬТЕРРА - Нуржанов, О.Д.; Абутова, А.Б. (SCIENCE and SOCIETY, 2024)
The paper obtained some results on the application of the numerical-analytic method of successive approximations to two-point boundary value problems for Volterra type integro-differential equations.
Keywords: numerical-analytic method; boundary value problem; integro-differential equations of Volterra type; boundary conditions of Cauchy-Nicoletti type